2004
DOI: 10.1038/sj.bjp.0705886
|View full text |Cite
|
Sign up to set email alerts
|

Triazine dyes are agonists of the NAADP receptor

Abstract: 1 NAADP has been shown to be a potent calcium-releasing second messenger in a wide variety of cell types to date. However, research has been hampered by a lack of pharmacological agents, with which to investigate NAADP-induced calcium release, and by the molecular identity of its cellular target protein being unknown. 2 In the present paper, the sea urchin egg model was used to investigate whether triazine dyes, which can act as nucleotide mimetics, can bind to the NAADP receptor, induce Ca 2 þ release and be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Soluble preparations bind NAADP with similar potency and selectivity as membranes (Berridge et al, 2002). Substantial enrichment can be obtained using affinity columns based on triazine dyes which act as NAADP agonists (Billington et al, 2004). The non-dissociating nature of NAADP binding allowed convenient tracking during several biochemical fractionation procedures and definition of key properties of the ligand-bound target.…”
Section: Naadp Binding Sitesmentioning
confidence: 99%
“…Soluble preparations bind NAADP with similar potency and selectivity as membranes (Berridge et al, 2002). Substantial enrichment can be obtained using affinity columns based on triazine dyes which act as NAADP agonists (Billington et al, 2004). The non-dissociating nature of NAADP binding allowed convenient tracking during several biochemical fractionation procedures and definition of key properties of the ligand-bound target.…”
Section: Naadp Binding Sitesmentioning
confidence: 99%
“…Again, unusually, the calculated native molecular weight differed depending on the fractionation method [23]. Attempts to purify the target protein to homogeneity have been conspicuously unsuccessful although Billington et al did achieve substantial enrichment following a one step fractionation [24]. Taken together, multiple lines of independent evidence suggested that NAADP targeted a novel calcium-permeable channel.…”
Section: Naadp Activates a Novel Channelmentioning
confidence: 99%
“…Homogenate can be prepared in bulk, and stored as frozen aliquots which remain responsive for many years. For all these reasons, the system has long been regarded as the ‘gold-standard’ for studying NAADP action [ 34 , 35 ], and has been frequently used to assess the action of molecules eliciting Ca 2+ release through each of the discrete, endogenous Ca 2+ mobilization pathways [ 13 , 30 , 32 , 33 , [37] , [38] , [39] , [40] , [41] , [42] ]. Although the system is clearly amenable to high throughput profiling, no screening campaign has, to our knowledge, yet been reported.…”
Section: Introductionmentioning
confidence: 99%